Business tourism in the focus of reversed trends - Ginevičius, Romualdas; Hausmann, Thomas; Schafir, Schlomo (Business: Theory and Practice, 2007)
The number and the costs of business trips grow. The first fairs specialized in this subject have been established in Dusseldorf and Berlin. The last fair, the second Business Travel Show in Dusseldorf, was visited by 110 exhibitors and twice as big as the fair one year ago. Focus of the fair was the important aspect of possibilities of cost reductions. It is understandable that especially companies of intense traveling amounts want to save money, as the German market of business trips reaches an enormously high level of turnover mentioned earlier of private holiday trips. The huge market of business trips and the increased cost consciousness are naturally a challenge for the tourism industry. The contribution available shows the importance and the management of this segment. Article in German. Geschäftstourismus im Fokus gegenläufiger Trends Auszug. Anzahl und Kosten von Geschäftsreisen wachsen. In Düsseldorf und Berlin etablieren sich die ersten deutschen Messen speziell für dieses Segment. Die vergangene 2. Business Travel Show in Düsseldorf z. B. präsentierte sich mit 110 Ausstellern doppelt so stark wie im Vorjahr. Im Mittelpunkt der Messe stand der wichtige Aspekt der Kostensenkungspotenziale. Verständlich, dass die Unternehmen mit starker Reiseintensität sparen wollen, denn immerhin erreicht der Markt der Geschäftsreisen in Deutschland das ausgesprochen hohe Umsatzniveau der privaten Urlaubstrips. Der große Markt der Geschäftsreisen und das gestiegene Kostenbewusstsein stellt die Tourismusindustrie natürlich vor Herausforderungen. Der vorliegende Beitrag zeigt die Bedeutung und das Management diese Segments auf. Schlüsselwörter: Begriff und Volumen des Geschäftsreiseverkehrs, Struktur des Geschäftsreisemarktes, Fluggesellschaften, Hotellerie, Mietwagenunternehmen, Deutsche Bahn AG.